Effect of sidt2 Gene on Cell Insulin Resistance and Its Molecular Mechanism - Qian-Ying Xiong; Chao-Qun Xiong; Li-Zhuo Wang; Jia-Lin Gao (Journal of Diabetes Research)
Background. Sidt2 (SID1 transmembrane family, member 2) is a multiple transmembrane lysosomal membrane protein newly discovered in our previous study. In the previous study, we used gene targeting technique to make a mouse model of sidt2 gene knockout (sidt2-/-). It was found that sidt2-/- mice showed elevated fasting blood glucose and impaired glucose tolerance, showing a disorder of glucose metabolism, suggesting that sidt2 may be closely related to insulin resistance. We used 3T3-L1 adipocytes, C2-C12 myoblasts, and HEPA1-6 hepatoma cells as subjects to observe the effects of sidt2 on insulin-stimulated glucose uptake and the abovementioned insulin signal transduction pathways, and then to explore the effect of sidt2 on peripheral tissue insulin resistance and its possible molecular mechanism. Methods. (1) Lentiviruses with sidt2 gene knockout and puromycin resistance were constructed by Crispr/cas9 vector and transfected into 3T3-L1 adipocytes, C2-C12 myoblasts, and HEPA1-6 hepatoma cells to construct sidt2 knockout cell line model. (2) Glucose uptake of 3T3-L1 adipocytes, C2-C12 myoblasts, and HEPA1-6 hepatoma cells stimulated by insulin was detected by glucose detection kit, and the results were analyzed. (3) Sidt2 knockout group and control group of 3T3-L1 adipocytes, C2-C12 myoblast, and HEPA1-6 hepatoma cells were cultured according to the routine method. The total proteins of the above cells were extracted, and the expression of PAKT (thr308), PI3-K, and PIRS-1 (ser307) in the IRS-1 signaling pathway of the three groups was detected by western blot technique. Results. (1) The sidt2 elimination models of 3T3-L1 adipocytes, C2-C12 myoblasts, and HEPA1-6 hepatoma cells were successfully constructed. (2) It was found that the glucose uptake of cells in the sidt2 knockout group was lower than that in normal group under insulin stimulation through the detection of glucose concentration in the cell culture medium. (3) It was found that the expression of PAKT (thr308) and PI3-K protein decreased and the expression of PIRS-1 (ser307) protein increased in sidt2-/- group compared to the control group. Conclusions. sidt2 knockout can reduce glucose uptake in peripheral tissue under insulin stimulation, which may lead to peripheral tissue insulin resistance by affecting the IRS-1 signal pathway.